1999
DOI: 10.1002/(sici)1097-4636(1999)48:5<755::aid-jbm23>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of powder-free examination gloves to bacteriophage penetration

Abstract: The purpose of this study was to compare the resistance to viral penetration of powder-free synthetic examination gloves with powder-free latex examination gloves commonly used in hospitals. Because these gloves had no holes, this study examined viral penetration through a membrane. Using a standard bacteriophage penetration model, no bacteriophage penetration was detected through the membrane for any of the gloves tested. The new powder-free nitrile and polyvinyl chloride synthetic examination gloves provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…(8) The glove that failed with exposure to movement was reportedly accelerator free. The above studies indicate that nitrile exam gloves are variable in (1) physical integrity, (2) resistance to mechanical stress, (3) chemical resistance, and (4) composition. More research is needed to uncover the underlying causes for these observed disparities with nitrile exam gloves and to narrow the observed gaps in glove integrity and chemical resistance performance.…”
Section: Introductionmentioning
confidence: 91%
“…(8) The glove that failed with exposure to movement was reportedly accelerator free. The above studies indicate that nitrile exam gloves are variable in (1) physical integrity, (2) resistance to mechanical stress, (3) chemical resistance, and (4) composition. More research is needed to uncover the underlying causes for these observed disparities with nitrile exam gloves and to narrow the observed gaps in glove integrity and chemical resistance performance.…”
Section: Introductionmentioning
confidence: 91%
“…However, intact vinyl gloves provide protection comparable to that of latex gloves (359). Limited studies indicate that nitrile gloves have leakage rates that approximate those of latex gloves (368)(369)(370)(371). Having more than one type of glove available is desirable, because it allows personnel to select the type that best suits their patient-care activities.…”
Section: Gloving Policiesmentioning
confidence: 99%
“…Research studies comparing various properties of nonlatex materials to those of latex have been published and are readily found in the literature. For example, multiple authors have studied leakage of both latex and nonlatex gloves after clinical use,1–5 simulated use,6–10 or directly out of the box 11–13. Physical properties such as puncture resistance, tensile strength, stiffness, and ease of donning for various glove materials have been studied 2, 7, 9, 14, 15.…”
Section: Introductionmentioning
confidence: 99%